Antiviral Activity of a Small Molecule Deubiquitinase Inhibitor Occurs via Induction of the Unfolded Protein Response - Perry, Jeffrey W. (Public Library of Science, 2012)
Ubiquitin (Ub) is a vital regulatory component in various cellular processes, including cellular responses to viral infection. As obligate intracellular pathogens, viruses have the capacity to manipulate the ubiquitin (Ub) cycle to their advantage by encoding Ub-modifying proteins including deubiquitinases (DUBs). However, how cellular DUBs modulate specific viral infections, such as norovirus, is poorly understood. To examine the role of DUBs during norovirus infection, we used WP1130, a small molecule inhibitor of a subset of cellular DUBs. Replication of murine norovirus in murine macrophages and the human norovirus Norwalk virus in a replicon system were significantly inhibited by WP1130. Chemical proteomics identified the cellular DUB USP14 as a target of WP1130 in murine macrophages, and pharmacologic inhibition or siRNA-mediated knockdown of USP14 inhibited murine norovirus infection. USP14 is a proteasome-associated DUB that also binds to inositol-requiring enzyme 1 (IRE1), a critical mediator of the unfolded protein response (UPR). WP1130 treatment of murine macrophages did not alter proteasome activity but activated the X-box binding protein-1 (XBP-1) through an IRE1-dependent mechanism. In addition, WP1130 treatment or induction of the UPR also reduced infection of other RNA viruses including encephalomyocarditis virus, Sindbis virus, and La Crosse virus but not vesicular stomatitis virus. Pharmacologic inhibition of the IRE1 endonuclease activity partially rescued the antiviral effect of WP1130. Taken together, our studies support a model whereby induction of the UPR through cellular DUB inhibition blocks specific viral infections, and suggest that cellular DUBs and the UPR represent novel targets for future development of broad spectrum antiviral therapies.